Preparation of Alumina-Sphere-Supported Potassium Chabazite Zeolite Membrane with Excellent Potassium Extraction Performance at Room Temperature - Jie Ouyang; Heng Wei; Jin Hou (Membranes, 2022)
In this paper, a potassium chabazite (KCHA) zeolite membrane was prepared by coating KCHA zeolite on the surface of a porous alumina sphere. The performance of the KCHA zeolite membrane in extracting potassium from seawater and sea bittern at room temperature was studied in detail. The XRD results show that the prepared KCHA zeolite was a KCHA membrane. The EDS test indicated that the potassium content of the KCHA zeolite membrane reached a value of 18.33 wt.%. The morphology of the KCHA zeolite grown on the surface of the alumina sphere was similar to a sphere, and it had good symmetry. The potassium ion-exchange capacities of the KCHA zeolite membrane reached 32 mg/g in seawater and 77 mg/g in sea bittern at room temperature. Ion exchange between the ammonium ions and potassium ions in the KCHA zeolite membrane could be completed in a short time at room temperature. The KCHA zeolite membrane was proven to have good reusability in seawater and sea bittern. The selective ion-exchange mechanism of the KCHA zeolite membrane was controlled by a specific K+ ion memory.